거래적,변혁적 리더십이 팀 임파워먼트 및 성과에 미치는 영향 - 이성철; Sung Chul Lee; 김홍; Hong Kim (한국의류산업학회지, 2008)
The purpose of this study is to analyze whether transactional leadership and transformational leadership have an effect on team empowerment and performance. To this end, a survey was conducted from August 1 to 30 in 2008, among team members of fashion companies. The data was collected with 586 subjects, the statistical analysis methods were frequency analysis, reliability analysis, factor analysis and multiple regression analysis. The results of this study were as follows; First, contingent reward of transactional leadership had an effect on team empowerment factors and team performance factors. Second, charisma, individualized consideration and intellectual stimulation of transformational leadership had an effect on team empowerment factors and team performance factors. Third, team potency, team autonomy and team meaning of team empowerment had an effect on team performance factors.